New Interventions by silicone grease in synthesis. Issue 23 (24th August 2022) - Werner, Daniel; Rad, Nazli E.; Guo, Zhifang; Deacon, Glen B.; Junk, Peter C.
Abstract: In redox‐transmetallation protolysis (RTP) reactions in tetrahydrofuran (thf) between excess scandium or cerium metal, Hg(C6 F5 )2 and 3, 5‐dimethylpyrazole (Me2 pzH) in silicone greased Schlenk flasks, formation of the 3, 5‐dimethyl‐1‐pyrazolyl(dimethyl)siloxide (Me2 pzSiMe2 O) ligand was observed. Thus the former reaction gave [Sc2 (Me2 pz)4 (Me2 pzSiMe2 O)2 ] 1 in good yield, whilst the latter gave a mixture of [Ce4 O(Me2 pz)9 (Me2 pzSiMe2 O)2 ] 2 a, [Ce4 O(Me2 pz)11 ] 2 b, both mixed oxidation state species, and the Ce IV complex [Ce(Me2 pz)4 (Me2 pzH)] 2 c . Abstract :